Annex I: description of the action (including the logical framework of the action): Sanitary and Phytosanitary (SPS) measures action: Support to CARIFORUM States in furthering the implementation of their Economic Partnership Agreement - IICA, Bridgetown (Barbados) (2021)
The Action on Sanitary and Phytosanitary Measures (SPS) is one Component (Component 2) of the 11th EDF Programme titled “Support to CARIFORUM States in furthering the implementation of their Economic Partnership Agreement (EPA) commitments and in meaningfully reaping the benefits of the Agreement”. The overall objective of the 11th EDF EPA Programme is to contribute to the integration of the Caribbean Forum of the ACP Group of States into the World Economy. While the specific objective is the effective operation of the EPA.